Ethnicity and national integration in Nigeria: A study of Nigerian students in neutral setting - Ahmed, Abdullahi (2016)
Ethnicity is a divisive force in Nigeria’s socio-political development. It tends to distort and strain relations between individuals and groups in the country. It has resulted in the emergence of an ethnic psyche which promotes ethnic consciousness and separatism instead of national identity and ethos. The root of ethnicity is arguably linked to the country’s colonial history, the colonial masters employed ethnic cleavages as a means of divide and rule thus strengthening their dominance of Nigerians at the expense of nation-building. The aim of this study is to explore the experiences of Nigerian students of the country’s socio-political problems associated with ethnicity and their interactive relationships in a neutral setting as a way of understanding Nigeria’s ethnic problematic from their perspective. In the course of the study data was collected principally through observations and in-depth interview with forty students of different ethnic origin from the country’s six geopolitical zones. The data was analysed within the qualitative frame of analysis. The study found out that religion, prejudice, and poverty are critical variables that have been used as a tool by the political status quo to nurture mistrust among Nigerians. The study also unravelled the role of positive interpersonal relations in fostering unity of purpose and reducing ethno-religious discriminations and tensions among Nigerian students. Educational pursuit is seen as an integrative mechanism that helps bind Nigerian students and facilitate attitudinal changes by imbibing new values that promote brotherhood in a foreign land. The study recommends sensitisation and reorientation in order to promote tolerance and understanding among Nigerians. As well as alleviating poverty through employment creation as a basis of fairness and social justice. In essence, good governance practices that promote transparency and accountability will also help in dousing intergroup conflicts.